STRATEGIC MANAGEMENT FUNCTION HUMAN RESOURCES - ISWANDIR ISWANDIR (JURNAL MITRA MANAJEMEN, 2014)
AbstractHuman Resources is a central factor in an organization. The shape and purpose of theorganization is made based on a variety of human interests and vision for the implementationof its mission is managed and maintained by humans .. So man is a strategic factor in all theactivities of the institution / organization. Human Resource Management means organizing,taking care of human resources is based on the vision of the company so that organizationalgoals can be achieved at its optimum for Human Resource Management is also part of theManagement Science (Management Science) who ask to manajemn function in theimplementation of planning processes, penrorganisasian, staffing, directing and controlling.Human resource management is a process of dealing with various problems on the scope ofthe employees, servants, laborers, managers and other workers to be able to support theactivities of the organization or company to achieve its intended purpose.